'What price do you put on your health?': Medical cannabis, financial toxicity and patient perspectives on medication access in advanced cancer. (6th November 2022) - Olson, Rebecca E.; Smith, Alexandra; Good, Phillip; Dudley, Morgan; Gurgenci, Taylan; Hardy, Janet
Abstract: Introduction: Following 2016 legislation permitting limited access to cannabis for research and medicinal purposes, the number of randomized clinical trials (RCTs) investigating the effectiveness of medicinal cannabis (MC) on symptom burden relief in cancer contexts has increased in Australia. This study aimed to understand the perceptions, hopes and concerns of people with advanced cancer regarding the future availability and regulation of MC in Australia. Methods: This qualitative study draws on semistructured interviews conducted between February 2019 and October 2020 in Brisbane, Australia, as part of an MC RCT substudy. Interviews were undertaken on 48 patients with advanced cancer in palliative care eligible to participate in an MC trial ( n = 26 participated in an RCT; n = 2 participated in a pilot study; n = 20 declined). Interviews included a discussion of patients' decision‐making regarding trial participation, concerns about MC and perceptions of future availability, including cost. Transcribed interviews were analysed inductively and abductively, informed by constructivist thematic analysis conventions. Results: Overall, participants supported making MC legally accessible as a prescription‐only medication. Fear of financial toxicity, however, compromised this pathway. Steep posttrial costs of accessing MC prompted several people to decline trial participation, and others to predict—if found effective—that many would either access MC through alternative pathways or reduce their prescribed dosage to enable affordable access. Conclusions: These findings suggest that—despite a relatively robust universal healthcare system—Australians are potentially vulnerable to and fearful of financial toxicity. Prevalent in the United States, financial toxicity occurs when disadvantaged cancer patients access necessary but expensive medications with lasting consequences: bankruptcy, ongoing anxiety and cancer worry. Interview transcripts indicate that financial fears—and the systems sustaining them—may pose a threat to RCT completion and to equitable access to legal MC. Such findings support calls for embedding qualitative substudies and community partnerships within RCTs, while also suggesting the importance of subsidisation to overcoming injustices. Patient or Public Contribution: A patient advisory committee informed RCT design. This qualitative substudy foregrounds patients' decision‐making, perceptions and experiences.